2019
DOI: 10.1002/jsfa.9593
|View full text |Cite
|
Sign up to set email alerts
|

In ovodelivery of various biological supplements, vaccines and drugs in poultry: current knowledge

Abstract: The technique of delivering various nutrients, supplements, immunostimulants, vaccines, and drugs via the in ovo route is gaining wide attention among researchers worldwide for boosting production performance, immunity and safeguarding the health of poultry. It involves direct administration of the nutrients and biologics into poultry eggs during the incubation period and before the chicks hatch out. In ovo delivery of nutrients has been found to be more effective than post‐hatch administration in poultry prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 152 publications
(308 reference statements)
1
32
0
1
Order By: Relevance
“…In ovo feeding is defined as direct administration of a compound into eggs during incubation ( Saeed et al., 2018 ). Studies demonstrated this technique supplied nutrients directly into chicken embryos which improved muscle development and growth, enhanced breast meat yield and feed utilization ( Bhanja et al., 2008 ), and decreased embryo mortality and morbidity by strengthening immunity and protection status against important infectious pathogens ( Madej and Bednarczyk, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In ovo feeding is defined as direct administration of a compound into eggs during incubation ( Saeed et al., 2018 ). Studies demonstrated this technique supplied nutrients directly into chicken embryos which improved muscle development and growth, enhanced breast meat yield and feed utilization ( Bhanja et al., 2008 ), and decreased embryo mortality and morbidity by strengthening immunity and protection status against important infectious pathogens ( Madej and Bednarczyk, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The technique of delivering various substances via the in ovo route is gaining wide attention among researchers worldwide (Saeed et al, ) to benefit from useful materials (Elnesr et al, ; Elwan et al, ) or to find out the negative effects of some substances, such as glyphosate, in an early stage. Glyphosate, N‐(phosphonomethyl) glycine, use is now widespread in the agricultural production, both in industrialized and in developing countries (Benbrook, ).…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic growth in poultry can be manipulated through in ovo administration of nutrients and natural bioactive compounds [1,2,3,4,5,6,7]. In ovo injection of such substances influences the pre- and post-hatching physiological status of broiler embryos, leading to improved hatchability, superior nutritional status of hatchlings, greater vigour and higher post-hatch growth [8,9].…”
Section: Introductionmentioning
confidence: 99%